Induction of specific Escherichia coli genes by sublethal treatments with alkylating agents. - Volkert, M R (1984)
Fusions of the lac operon to genes induced by treatment with sublethal levels of alkylating agents have been selected from random insertions of the Mu-dl(ApRlac) phage by screening for induction of beta-galactosidase activity in the presence of methyl methanesulfonate. Genetic analysis reveals that these fusions resulted from insertion of Mu-dl(ApRlac) into two regions of the chromosome. One region (aidA) is near his and, based on phenotypic effects, appears to represent insertion into the alkA gene. The other region (aidB) is in the 92.3- to 98-min region, which harbors no previously identified genes involved in repair of alkylation damage. The aidB fusions caused increased resistance to alkylating agents and caused little or no change in the biological effects of adaptation to alkylating agents. Unlike the aidA fusions, aidB fusions showed increased beta-galactosidase activity in untreated cells in a growth phase-dependent fashion. The ada-5 mutation, which blocks expression of the adaptive response, decreased induction of beta-galactosidase activity in both aidA and aidB fusions after alkylation treatments. Thus, both aidA and aidB share with adaptive response a common regulatory mechanism involving the ada gene. The growth phase-dependent control of the aidB fusions, however, is unaffected by ada, suggesting that a second regulatory mechanism exists that controls only aidB.